Monetary Policy, Debt and the Cyclical Behavior of Inventories - Ismail, Abdul Ghafar; Bahari, Zakaria (Master of Management, Faculty of Economics and Business, Universitas Gadjah Mada, 2007)
An earlier study on the determinants of inventories investment has been proposed by Lovel (1961). However, the study fails to mention the effects of financial variables. The puzzle prevails on account of imperfect capital markets. This implies that interest rate generally affects inventory investment indirectly through the debt channel. For instance, in the period of tight monetary policy, increasing interest rates have a negative impact on the present value of firmsâ collateralizable net worth. In addition, they also weaken firmsâ balance sheets as interest expenses also rise up. In imperfect capital markets, this fact indicates an increase in the amount of external financing that firms need, a rise in the premium on external financing that they face, and a reduction in their accumulation of assets, their spending and their production. Given the low adjustment cost that characterizes firms, it will be inventories that firms will initially reduce. Therefore, this paper is contributes to the issue of monetary policy transmission in Malaysia. Our specific attention is limited to the channel of monetary policy on a firmâs inventory. Using micro data, we try to take into account the relevance of the firmâs balance sheet conditions in the transmission of monetary policy.